MEHRAN NEJATI HONOURED BY PUBLONS, RECEIVES CERTIFIED SENTINELS OF SCIENCE AWARD 2016 - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
PENANG, 3 October 2016 – A lecturer at the Graduate School of Business (GSB), Universiti Sains Malaysia (USM), Dr. Mehran Nejati today received the Certified Sentinels of Science Award 2016 in being one of the top 10% of researchers contributing to the peer review in the field of Business, Management and Accounting by Publons.